2015
DOI: 10.1111/nana.12083
|View full text |Cite
|
Sign up to set email alerts
|

Partitioned identities? Everyday national distinctions inNorthernIreland and theIrish state

Abstract: How does political structure affect ethno‐national distinction? Partitioned societies are a good test case where we can see the effects of changed socio‐political circumstances on historically inherited distinction. This article takes nominally identical distinctions of nationality and religion with common historical roots and shows how they are differentially understood in two polities partitioned in 1920: Northern Ireland, a devolved region of the United Kingdom, and the Irish state. Using a data base of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Some intra-variety exists within these groups of course, along social class lines of which McIlroy is one example. He declares himself a Catholic more comfortable with British culture owing to his father's identity but, in general, most inhabitants take the Protestant/Catholic and Irish/British distinctions as a form of self-positioning (Todd 2015;ARK 2017). While religion and identity are deeply connected in NI, sport, neighbourhood affiliation and educational background also play a significant role in identity and divisions.…”
Section: 'Ireland' Identity and Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…Some intra-variety exists within these groups of course, along social class lines of which McIlroy is one example. He declares himself a Catholic more comfortable with British culture owing to his father's identity but, in general, most inhabitants take the Protestant/Catholic and Irish/British distinctions as a form of self-positioning (Todd 2015;ARK 2017). While religion and identity are deeply connected in NI, sport, neighbourhood affiliation and educational background also play a significant role in identity and divisions.…”
Section: 'Ireland' Identity and Sportmentioning
confidence: 99%
“…While religion and identity are deeply connected in NI, sport, neighbourhood affiliation and educational background also play a significant role in identity and divisions. For instance, Todd (2015) found that identity-as-orientationencompassing a value perspective, assumptions and expectationsis prevalent in NI where people are guarded in their use of the national 'we', and much more likely to speak of 'I'. For many Northerners then, national identity is much more a project or orientation than a shared collective feeling, not least because of the unstable Around the time of the vote, he commented 'if I'm Northern Irish, what's better?...To be part of the UK and not be in the EU?…”
Section: 'Ireland' Identity and Sportmentioning
confidence: 99%
“…So too in the Irish case, we see multiple informal criteria of being Irish – from place of birth and socialization through to associational practices and interactive norms – with meaning and reference intertwined. These are popularly understood in variable geometry form such that all criteria are relevant, some sub-set of them is necessary, but which and how many are sufficient for acceptance of a claim to be Irish is very much a matter of context and negotiation (Todd, 2015: 30).…”
Section: The Dual Faces Of Identity and Differencementioning
confidence: 99%
“…The conventional rules, the ‘grammars of nationality’ as Todd (2015: 27–31) has called them, are not simply official categorizations. They are made in social practice, with multiple areas of dispute, uncertainty, and discretion of interpretation.…”
Section: Contestation and Consensusmentioning
confidence: 99%
“…Political science has looked at how ethnic and national landscapes are remapped in contentious politics (see for example Beissinger, 2002; Brubaker, 2002; Coakley, 2012; McAdam et al, 2001). But there are also ways of reinterpreting the meanings of nationality and ethnicity that make boundaries more or less exclusivist, more or less permeable, more or less salient; this does not simply shift categorical schema but reinterprets their meaning (Hoewer, 2014; Lamont and Mizrachi, 2011; Mitchell and Ganiel, 2011; Shenhav, 2006; Todd, 2015). Moreover, the Self/Other opposition often relies on a Western metaphysical conception of actors as independent and discreet entities, rather than as correlated and co-embedded parts of an organic whole, constituted by their interrelationship (Ling, 2013; Qin, 2016).…”
Section: Introductionmentioning
confidence: 99%